Teacher Emotional Agency: Appropriating the Learning Management System amid the Pandemic - Romerosa, Peter; Arzadon, Maria Mercedes E.; Camposano, Clement (Philippine Journal of Education Studies (formerly the Education Quarterly); Vol 2 No 2 (2024): Philippine Journal of Education Studies, 2024)
This study examines how the emotional agency of teachers is achieved in appropriating the Learning Management System (LMS) policy of a non-sectarian private institution in an urban area during the COVID-19 pandemic using digital ethnography. The results reveal that teacher emotional agency involves personal, pedagogical, and technological capacities, emotions, and contextual factors. Specifically, teacher emotional agency is achieved by nurturing "kaagapay" relationships with parents, peers, and school, negotiating top-down policies, and recasting teaching and learning in Online Distance Learning. The contextual factors that mediate teacher emotional agency in the appropriation of LMS policy include the following: 1) spatial geographical factors, referring to the shift of the learning environment from the traditional classroom to a virtual learning setting; 2) cultural factors, comprised of learning marketing or entrepreneurship skills, digital competence, and online teaching strategies; 3) material factors, involving using the LMS, meeting applications such as Zoom and Google Meet, the internet, and digital devices for online distance learning; and 4) social factors, referring to greater parental participation and learner agency. The study proposes a conceptual model highlighting the role of teachers’ emotional agency in appropriating the LMS policy amid a crisis.